THE EFFECT OF PREZI-ASSISTED PRESENTATION MEDIA ON STUDENTS’ CRITICAL THINKING SKILLS IN THE COORDINATION SYSTEM TOPIC FOR GRADE XI AT SMA NEGERI 8 PEKANBARU - Sanni H. Simangunsong; Mariani Natalina L; Darmadi (Yayasan Amanah Nur Aman, 2026)
The low critical thinking skills of students in biology learning motivated this study. This issue occurs due to several factors, one of which is the use of presentation media that does not adequately support the learning process. The purpose of this study was to determine the effect of Prezi presentation media on students’ critical thinking skills in the coordination system topic for Grade XI at SMA Negeri 8 Pekanbaru. This study employed a quasi-experimental method with a pretest–posttest control group design. The samples were classes XI.10 and XI.8, selected using purposive sampling. Prezi presentation media was used in the experimental class during the learning process, while the control class used PowerPoint media commonly used by the teacher. The research instruments included a critical thinking skills test and an observation sheet. The results showed that the critical thinking skills of students in the experimental class were higher than those in the control class. The average pretest score of the experimental class was 43.5 compared to 39.3 in the control class, while the average posttest score was 81.8 in the experimental class and 68.8 in the control class. The data obtained were analyzed using an independent sample t-test, resulting in a significance value (2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that the use of Prezi-assisted presentation media has a significant effect on students’ critical thinking skills in the coordination system topic for Grade XI at SMA Negeri 8 Pekanbaru.